2022
DOI: 10.3991/ijet.v17i07.30405
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Application of a Major-Specific Knowledge Graph Based on Big Data in Education

Abstract: The main problems lying in the learning process of learners in different majors are that they study blindly and do not have a complex knowledge structure, which are seriously affecting their learning effects. But if a knowledge graph can be modeled for the major-specific curriculum system using the quantitative method from the perspective of knowledge network, it may be able to improve the existing teaching problems and optimize the teaching quality. The existing major-specific knowledge graphs were all constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In recent years, new theories have been developed [20], [21], [22], [23], [24], [25] suggesting there are alternative ways of formalizing mathematical ideas and highlighting the relevant role of different sensory modalities in the processes of abstraction, and in general, in the construction of concepts from simple to complex [26], [27]. These theories are supported by numerous studies that were carried out during the so-called "brain decade" (1990-2000) that bring out the functioning of the motorsensory system of the brain in the development of conceptual knowledge and examine how brain physiological functions support cognitive processes [28], [29], [30], [31], [32].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, new theories have been developed [20], [21], [22], [23], [24], [25] suggesting there are alternative ways of formalizing mathematical ideas and highlighting the relevant role of different sensory modalities in the processes of abstraction, and in general, in the construction of concepts from simple to complex [26], [27]. These theories are supported by numerous studies that were carried out during the so-called "brain decade" (1990-2000) that bring out the functioning of the motorsensory system of the brain in the development of conceptual knowledge and examine how brain physiological functions support cognitive processes [28], [29], [30], [31], [32].…”
Section: Methodsmentioning
confidence: 99%
“…If the value of the boolean expression of the conditional operator is true, then information about the partially generated solution is not displayed. If a solution is found and the process is not interrupted by the user, the source code in the if statement block (lines [15][16][17][18][19][20] redraws the graph and displays information about the values of the variables involved in the process, for example, the number of edges covered (CoverEdgeCount), the number of vertices used (CoverVertexCount), and the elapsed time determined by the difference between the values of the variables tE and tS.…”
Section: Fig 1 Global Declarations Source Codementioning
confidence: 99%
“…Many transportation problems, site allocation problems, optimal route selection problems or service center placement problems, and problems related to creating optimal schedules and timetables are also described by graphs and solved by the corresponding algorithms [9][10][11][12][13]. Graphs are also used for modeling in the field of learning [14][15][16] and assessment [17]. In this way, various physical, chemical, economic and managerial systems and processes can be successfully represented and studied with graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Cui and Yu [8] examined the effects of knowledge graphs on fostering deep learning in a flipped classroom, which indicated that learning with the help of knowledge graphs can achieve better performance in the students' learning products. In a similar way, Wu and Jia [9] investigated the concrete construction and the corresponding applications of the English major-specific knowledge graphs through extensive data sources in an educational domain and verified the interconnection of nodes within structured knowledge graphs. In summary, to provide a more intuitive presentation of the knowledge graph review studies, a list of existing review articles is presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%